2014
DOI: 10.4239/wjd.v5.i6.777
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and cellular replacement therapy: Expected clinical potential and perspectives

Abstract: Diabetes mellitus (DM) is the most prevailing disease with progressive incidence worldwide. Despite contemporary treatment type one DM and type two DM are frequently associated with long-term major microvascular and macrovascular complications. Currently restoration of failing β-cell function, regulation of metabolic processes with stem cell transplantation is discussed as complements to contemporary DM therapy regimens. The present review is considered paradigm of the regenerative care and the possibly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
(89 reference statements)
0
8
0
1
Order By: Relevance
“…Sun and colleagues reported that HUMSCs could decrease inflammatory cytokines by suppressing NLRP3 inflammasome activation in type 2 diabetes rats [19]. Moreover, HUMSCs are currently under clinical research to evaluate the safety and efficacy of treatment of type 2 diabetes [20]. However, the roles of HUMSCs in DR have not been elucidated, and to probe the potential mechanisms is indispensable for the clinical application.…”
Section: Ivyspringmentioning
confidence: 99%
“…Sun and colleagues reported that HUMSCs could decrease inflammatory cytokines by suppressing NLRP3 inflammasome activation in type 2 diabetes rats [19]. Moreover, HUMSCs are currently under clinical research to evaluate the safety and efficacy of treatment of type 2 diabetes [20]. However, the roles of HUMSCs in DR have not been elucidated, and to probe the potential mechanisms is indispensable for the clinical application.…”
Section: Ivyspringmentioning
confidence: 99%
“…Human uMSCs are currently under clinical investigations to treat diabetes ( Berezin, 2014 ). Although the preliminary data from both T1D and T2D studies are promising ( Hu et al, 2013 ; Kong et al, 2014 ), the mode of action remains to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, EPCs isolated from peripheral blood of the patients with known CAD have exhibited an impaired migratory and weak proliferative response [50], which have confirmed being of "EPC impaired phenotypes" pre-existing in subjects with CV risk factors prior established CV disease [55,56]. However, the circulating level of EPCs in patients with established higher CV risk is very variable and does not fully correlate with number of CV risk factors [57,58], although number of BM-EPCs has closely predicted asymptomatic atherosclerosis [59,60] and CV disease [61].…”
Section: Endothelial Progenitor Cells and CV Riskmentioning
confidence: 85%